2016
DOI: 10.17161/bi.v11i0.5053
|View full text |Cite
|
Sign up to set email alerts
|

Completeness of Digital Accessible Knowledge of Plants of Benin and Priorities for Future Inventory and Data Discovery

Abstract: Abstract.-Discovery of and access to primary biodiversity data are critical components in informed decision-making regarding sustainable use of biological resources and conservation of biodiversity. Primary biodiversity data are increasingly available from Benin, but information about completeness of this information across the country is still lacking for most groups. This study analyzed the Digital Accessible Knowledge regarding the plants of Benin to identify gaps in both geographic and environmental dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
5
9
0
Order By: Relevance
“…Our results are supported by those of Ballesteros-Mejia et al(2013), who reported positive effects of tra c access, road density, and tourism on the inventory completeness of tropical insects in Sub-Saharan Africa. Our results are also supported by a previous study byGanglo and Kakpo (2016) on plant data completeness in Benin, where they found that data completeness was positively impacted by the density of roads and waterways. Our results are also in line with those ofKadmon et al (2004) and Souza-Baena et al (2013) in their respective studies on plant species data of Israel and plant data completeness of Brazil, where they found that road bias affected the distribution of data.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Our results are supported by those of Ballesteros-Mejia et al(2013), who reported positive effects of tra c access, road density, and tourism on the inventory completeness of tropical insects in Sub-Saharan Africa. Our results are also supported by a previous study byGanglo and Kakpo (2016) on plant data completeness in Benin, where they found that data completeness was positively impacted by the density of roads and waterways. Our results are also in line with those ofKadmon et al (2004) and Souza-Baena et al (2013) in their respective studies on plant species data of Israel and plant data completeness of Brazil, where they found that road bias affected the distribution of data.…”
supporting
confidence: 91%
“…In line with the present work, data completeness analyses were diversely achieved at national and regional scales across Africa. In Benin, data completeness analysis was achieved on the DAK of the plants to guide future inventory and data discovery efforts in the country (Ganglo and Kakpo, 2016). From the results obtained, many spatial and environmental gaps exist in the completeness of the data, particularly in the northernmost departments of the country.…”
mentioning
confidence: 99%
“…Knowledge of the spatial and temporal distribution of a species is key for evaluating extinction risks and forecasting possible future threats from factors such as climate change (Pacifici et al 2015;Urban 2015;Ganglo and Kakpo 2016). Ecological niche models (ENMs) are used to understand ecological requirements of species, predict geographic distributions, select areas for conservation and forecast effects of environmental change (Peterson et al 2011;Ganglo et al 2017;Djotan et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Biodiversity information for the West African region has heretofore been characterized by the existence of major gaps across geography (Koffi et al, 2015;Asase and Peterson, 2016;Ganglo and Kakpo, 2016) and, more broadly, across Africa (Dauby et al, 2016;Sosef et al, 2017). In this sense, the WAP Initiative has made major and significant progress, adding >190,000 new biodiversity records to the information available for the plants of the region.…”
Section: Was the West African Plants Initiative Successful?mentioning
confidence: 99%